2010
DOI: 10.1051/0004-6361/200912103
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric radius and limb darkening of the asteroseismic red giantη Serpentis with the CHARA Array

Abstract: Context. The radius of a star is a very important constraint to evolutionary models, particularly when combined with asteroseismology. Diameters can now be measured interferometrically with great precision (better than 1%), but the center-to-limb darkening (CLD) remains a potential source of bias. Measuring this bias is possible by completely resolving the star using long-baseline interferometry, and has only been achieved for a handful of stars. Aims. The red giant η Ser (K0III-IV) is a particularly interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
7
2
Order By: Relevance
“…9). For comparison, the power law exponent α = 0.23 ± 0.05 found by Mérand et al (2010) in the K band for the red subgiant η Ser (K0III-IV) is higher than the power law exponent we find for α Cen B in the H band. η Ser is cooler than α Cen B and its effective gravity is significantly lower (T eff = 4955 K, log g = 3.2; Hekker & Meléndez 2007).…”
Section: Comparison With Literature Models and The Suncontrasting
confidence: 76%
“…9). For comparison, the power law exponent α = 0.23 ± 0.05 found by Mérand et al (2010) in the K band for the red subgiant η Ser (K0III-IV) is higher than the power law exponent we find for α Cen B in the H band. η Ser is cooler than α Cen B and its effective gravity is significantly lower (T eff = 4955 K, log g = 3.2; Hekker & Meléndez 2007).…”
Section: Comparison With Literature Models and The Suncontrasting
confidence: 76%
“…Moreover, the model dependence on the diameter determination has also an impact on the reliability of the existing catalogs of calibrator stars for interferometry that are based on red giants with similar parameters to those studied in this work. In fact, the formal high accuracy reached on diameter determination (a fraction of 1%, Mérand et al 2010) is based only on 1D models, while we show that the correction reported in Table 3 can have a sizeable impact.…”
Section: Estimation Of Diameter Correction: 1d Versus 3d Modelsmentioning
confidence: 68%
“…This measurement is challenging, and in some cases, such as the Kepler-138 system, the required precision is unattainable by current instrumentation. Alternatively, a direct measurement of the radius can be obtained from interferometry (Ligi et al 2016), although a slight dependence with the limb-darkening exists if the star is not completely resolved (Mérand et al 2010). This technique is not accessible for Kepler targets, but will be determinant for TESS and PLATO targets.…”
Section: Discussionmentioning
confidence: 99%